Washing effects on electrochemical performance and storage characteristics of LiNi0.8Co0.1Mn0.1O2 as cathode material for lithium-ion batteries - Xiong, Xunhui; Wang, Zhixing; Yue, Peng; Guo, Huajun; Wu, Feixiang; Wang, Jiexi; Li, Xinhai (Journal of power sources, 2013)
The effect of water washing on LiNi0.8Co0.1Mn0.1O2 cathode is extensively studied with respect to the electrochemical properties, structural stabilities, and storage characteristics. Water washing can improve the cycling performance and structural stability of LiNi0.8Co0.1Mn0.1O2 material in electrolyte, although with a slight deleterious effect on the capacity. Storage tests of the 4.3 V charged electrodes at 90 °C after 30 days show that Ni, Co, Mn in fresh and washed samples are dissolved in electrolyte, but the amount of dissolved Ni4+ ions after washing decreases by 31.5% compared with the fresh cathode. Moreover, the fresh sample transforms into the spinel phase with a Fd3m space group, whereas the washed sample remains as a layered hexagonal phase with an Rm3¯ space group. FTIR spectroscopy, transmission electron microscope (TEM), X-ray diffraction (XRD) and electrochemical studies indicate that the washed materials become more easily attached upon exposure to air, accompanied by significant increase in cationic disorder and NiO-like cubic phase near surface. Water washing can improve the cycling performance and structural stability of LiNi0.8Co0.1Mn0.1O2 material in electrolyte, although with a slight deleterious effect on the capacity. Moreover, the fresh sample transformed into the spinel phase with a Fd3m space group, whereas the washed sample remained as a layered hexagonal phase with an R3¯m space group when storing in electrolyte at 90 °C for 7 days at charged state. However, the washed materials became more easily attached upon exposure to air, accompanied by significantly increased cationic disorder and NiO-like cubic phase near surface. [Display omitted] ► The effect of water washing on fresh LiNi0.8Co0.1Mn0.1O2 cathode was firstly studied. ► Water washing improved the cycling performance and structural stability of material. ► Water washing resulted in a slight deleterious effect on the capacity. ► Water washing made material much less resistant to H2O and CO2 when storing in air.